1987
DOI: 10.3171/jns.1987.66.2.0244
|View full text |Cite
|
Sign up to set email alerts
|

Hormone production in clinically nonfunctioning pituitary adenomas

Abstract: Pituitary tumors in which no excess hormone secretion can be identified clinically have been considered as nonfunctioning or null-cell adenomas. Immunocytochemical data presented here suggest that many of these tumors contain subunits of the glycoprotein hormones. Of 160 patients referred for pituitary surgery, 37 (23%) had no evidence of excess hormone secretion on preoperative endocrine evaluation. Immunocytochemical staining of these tumors was carried out using antibodies specific for prolactin, growth hor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(50 citation statements)
references
References 43 publications
2
48
0
Order By: Relevance
“…It has been reported that the incidence of SCA among NFA ranged between 6 to 8.1% [1,10]. The present study showed the higher incidence (20%) of SCA (6 out of 30 NFAs), suggesting that SCA is not so unusual as previously thought.…”
Section: Discussionsupporting
confidence: 63%
“…It has been reported that the incidence of SCA among NFA ranged between 6 to 8.1% [1,10]. The present study showed the higher incidence (20%) of SCA (6 out of 30 NFAs), suggesting that SCA is not so unusual as previously thought.…”
Section: Discussionsupporting
confidence: 63%
“…Light and electron microscopy studies show the presence of secretory granules in neoplastic pituitary tissue (5). RNA anal-ysis (6-9) and immunocytochemistry (10)(11)(12) also confirm the synthesis and secretion of intact gonadotropins or their subunits by a subset of nonfunctioning pituitary adenomas.…”
Section: Introductionmentioning
confidence: 95%
“…Gonadotropin-secreting adenomas (GSAs) account for w12-17% of surgically treated pituitary adenomas (1,2). Since GSAs show no signs of endocrine hyperfunction, their clinical characteristics and long-term outcome differ from those of other pituitary adenomas, which frequently involve extrasellar extension with mass effects, visual disturbances, and pituitary dysfunction (3).…”
Section: Introductionmentioning
confidence: 99%